P989 Speckle tracking echocardiography for assessment of baseline myocardial dysfunction and remodelling following tricuspid valve surgery in adults with Ebsteins anomaly. (17th January 2020) - Ostenfeld, E; Ricci, P; Fusco, F; Flick, C; West, C; Gatzoulis, M A; Babu-Narayan, S V; Li, W
Abstract: Funding Acknowledgements: Swedish Heart-Lung Foundation, Swedish Society of Medicine, Swedish Heart Association, Skåne University Hospital, Region Skåne, and Lund University Background: Ebstein's anomaly (EA) is due to failure of tricuspid valve (TV) delamination and often associated with RV myopathy. Conventional echocardiographic measurements of systolic ventricular function such as LV EF, and tricuspid annular plane systolic excursion/fractional area change (TAPSE/FAC) are load dependent and may therefore not reflect true myocardial function. Speckle tracking echocardiography (STE) evaluates more subtle myocardial deformation globally and on a regional level. Due to being load independent STE may be the most appropriate way to determine myocardial effects of EA intervention for which data in adults are limited. Purpose: We aimed to study biventricular myocardial function before and after tricuspid valve repair/replacement (TVR) in adults with EA with both STE-derived peak systolic global and regional longitudinal strain (GLS; RLS) and conventional echocardiography. Methods: A retrospective study of 18 EA patients (55.6% women), who underwent surgical TV repair/replacement (3/15; age at operation: 39 ± 12y) between 2005-2017 was performed. 2D longitudinal strain and conventional assessment of LV and RV function were assessed pre-TVR, and at 1- and 2-years post-TVR. LV and right ventricular (RV) segments were graded for STE assessment feasibility (0-3: no visualisation-optimal). Segments scored 0 were excluded from the strain analysis. Biventricular GLS and RLS were measured by semi-automated tracking. Results: Compared to pre-TVR, LVEF improved after TVR at 1 year (Table 1, p = 0.03), but this was not sustained and returned to baseline after 2 years. TAPSE declined 1-year post-TVR with no further change after 2 years (Table 1). RVFAC did not differ pre- and post-TVR. LV GLS and RLS were low pre-TVR without amelioration at 1 or 2 years after TVR (Table 1). RV GLS deteriorated from pre-TVR to 1-year post-TVR with only minor amelioration after 2 years (p = 0.03). RV RLS showed a decrease at basal and mid free wall 1-year post-TVR, and at basal free wall, the mid free wall and the mid septum after 2 years (Table 1). Only, one segment improved in RLS from 1 to 2-year post-TVR (p = 0.03). Least feasible segments were LV apical lateral (both pre- and post-TVR), RV mid (pre-TVR and 1y post-TVR) and apical free wall (pre-TVR, 1y and 2y post-TVR) (all, median score 1). Conclusions: In adult patients with EA, LV GLS was reduced before and unchanged after surgery despite preserved EF, and LVEF initially improved but returned to baseline values with time. Although TV surgery reduced the degree of TV regurgitation and RV size, it might have unmasked a potential RV myocardial disease. Both RV longitudinal strain and TAPSE were reduced 1 and 2 years post-TVR with limited recovery of RV longitudinal strain, but not of TAPSE, between 1 and 2 years post-TVR. Speckle tracking echocardiography (STE) is a feasible and a sensitive, load independent method in detecting biventricular myocardial dysfunction and time course of remodelling after surgery.